The Effect of Rosetta Stone Application on Student’s English Reading Comprehension - Zahrotun Nufus; Mutiarani; Sarwenda (Rumah Riset Publisher, 2023)
This study investigated the use of Rosetta Stone application as a media in EFL students’ reading comprehension. This study implemented a quantitative approach in achieving the research objective which is finding out the effect size of Rosetta Stone application on students’ reading comprehension. The experimental design was carried out by using pre-test and post-test as the instruments to collect the data. The data from the pre-test and post-test were analyzed by using SPSS. The Cohens’d effect size in paired sample effect size determined the significant effect of the implementation of Rosetta Stone application on students’ reading comprehension. This study was conducted in SMPN 4 Tangerang Selatan. This research involved ten classes as the population, with a sample of class 8.1 that consisted of 42 EFL students. Based on the analysis of the data, the mean of the post-test is higher than the pre-test with a difference of 36.35 points. The effect size is considered high since 3.260 is higher than 1 (>1). Therefore, the use of Rosetta Stone application has a high effect on students’ reading comprehension. It is recommended for teachers especially EFL to implement Rosetta Stone application in students’ reading comprehension. Further studies are advised to investigate the students’ perception, as well as the advantages and limitations of Rosetta Stone application on students’ reading skills.